Metatony in monosyllables - Kortlandt, Frederik (Baltistica, 2014)
There are two chronological layers of metatonical circumflex in monosyllables, viz. an early Balto-Slavic layer which is reflected e.g. in Lith. dė̃s, jõs, duõs and a recent Aukštaitian layer which is found e.g. in nom.pl. tiẽ, acc.pl. tuõs, inst.sg. tuõ. Leskien’s law was younger than the former but older than the latter. This analysis is not based on a comparison with Slavic or Indo-European but on the internal evidence of the East Baltic languages.The Baltic future represents two Indo-European paradigms, viz. an s‑present with accentual mobility between the suffix and the ending and an s‑aorist with fixed stress on the root and monosyllabic lengthening in the 2nd and 3rd sg. forms. Both of these formations have exact correspondences in the Old Irish subjunctive. They must have existed side by side in Proto-Baltic in view of Prussian teīks ‘make!’ beside postāsei ‘you will become’.The circumflex of Latvian sā̀ls and gùovs shows metatonical length as a result of monosyllabic lengthening. There is no evidence for a PIE phoneme *a in sā̀ls, zùoss and nãss, nor for the vowel *e in the PIE paradigm of gùovs, nor for a PIE paradigm with fixed stress in the case of gùovs, nãss and zvrs, nor for a generalization of the original nom.sg. instead of acc.sg. accentuation in sā̀ls and nãss.